Giving Patients Choices During Involuntary Admission: A New Intervention - Burn, Erin; Conneely, Maev; Leverton, Monica; Giacco, Domenico (Frontiers in Psychiatry, 2019)
Background: People who receive involuntary treatment are some of the most vulnerable in psychiatric services. They are more likely to have poorer social and clinical outcomes and to be disillusioned with and disengaged. Research indicates that patients’ experience in the first week of involuntary treatment is a critical period: a better experience of care in the first week predicts better quality of life and reduced readmission one year later. Patients have identified involvement in clinical decisions as key to improving their experience of care. The aim of this study was to test the feasibility and acceptability of a novel intervention to facilitate involvement in decision-making called OPeNS (Options, Preferences, Negotiate, and Summarise). Methods: This was a mixed method study. The OPeNS intervention was developed based on previous research by a multidisciplinary team. Clinicians were trained to deliver it to involuntary inpatients. Feasibility indexes (rates of participation in the intervention and time required to deliver it) were collected. Patients (N=14) and clinicians (N=5) provided qualitative data on their experience of the intervention in semi-structured interviews which were analysed using thematic analysis. Results: The OPeNS intervention was found to be acceptable by both patients and clinicians and feasible to conduct within the first week of involuntary treatment. Patients and clinicians’ experiences of the intervention fall into two themes: “Enabling a different dynamic” and “Clashing with usual practices and priorities”. Conclusion: The OPeNS intervention provides a structure that can be used by clinicians across disciplines to facilitate involving involuntary patients in decision-making. Although challenges related to changing usual practices were identified, the intervention was received positively and was feasible to conduct in the first week of involuntary treatment.